INTERNATIONAL ASSESSMENT SYSTEMS AND THE PURPOSE OF THE PISA SYSTEM IN PHYSICS (Web of Teachers: Inderscience Research, 2024)
This article discusses the importance, place and role of PISA in the teaching of physical sciences within the framework of international assessment programs.